Living environments: Gender violence in the Peruvian highlands - Pacheco-Luza, Edgard; Álvarez-Becerra, Rina; Acevedo-Duque, Ángel; Bustamante-Cabrera, Gladys (Revista de Ciencias Sociales, 2024)
This research addresses the concerning living conditions of indigenous women and girls in the Peruvian highlands, who face situations of violence and discrimination that contradict the United Nations Agenda's Goal 3 (Health and Well-being). The main objective was to analyze the perceptions of indigenous women (Aymara and Quechua) who are victims of intimate partner violence regarding the barriers to seeking formal institutional help. A qualitative methodology based on grounded theory was employed, with a reflexive thematic analysis design. Seventeen interviews were conducted with women aged 22 to 60 who met the criteria of having experienced intimate partner violence and self-identifying as Aymara or Quechua. Key findings include self-silencing behaviors, fear of the aggressor’s reaction and the consequences of seeking help, as well as the minimization and justification of the violence, which perpetuate the abuse. Additionally, a cultural stigma was identified that questions women’s rights over their traditional gender roles, thus hindering their well-being and safety. Social barriers at multiple levels further prevent these women from seeking formal help, reinforcing the cycle of violence.